Themes for a latin american bioethics - Rodríguez Yunta, Eduardo (Acta Bioethica, 2009)
The present work considers the philosophical basis of bioethics as a discipline, method and movement from its historical context, and proposes bioethical themes in relation with the social and cultural context of life in Latin American.